On the channels of foreign aid to corruption - Simplice A. Asongu; Mohamed Jellal (African Governance and Development Institute (AGDI), 2013)
The debate by Okada & Samreth (2012, EL) and Asongu (2012, EB; 2013, EEL) on 'the effect of foreign aid on corruption' in its current state has the shortcoming of modeling corruption as a direct effect of development assistance. This note extends the debate by assessing the channels of foreign aid to corruption in 53 African countries for the period 1996-2010. Two main findings are established to unite the two streams of the debate. (1) Foreign aid channeled through government's consumption expenditure increases corruption. (2) Development assistance channeled via private investment and tax effort decreases corruption. It follows that foreign aid that is targeted towards reducing corruption should be channeled via private investment and tax effort, not through government expenditure. Our results integrate an indirect component and reconcile the debate by showing that, the effect could either be positive or negative depending on the transmission channel.
Keywords: B20; F35; F50; O10; O55; 330; Foreign Aid; Political Economy; Development; Africa